Analisis Tingkat Kognitif Pada Soal Buku Teks IPA Kelas VII Berdasarkan Taksonomi Bloom (Revisi) - Sholihah, Afifah Maratush; Astuti, Dwi Setyo (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study investigated the distribution of cognitive levels within the questions of the Grade VII science textbooks published by the Ministry of Education and Culture in 2021, using the revised Bloom’s taxonomy as an analytical framework. The revised Bloom’s taxonomy categorizes cognitive processes into six distinct levels: C1 (remembering), C2 (understanding), C3 (applying), C4 (analyzing), C5 (evaluating), and C6 (creating). This study adopted a descriptive research design with a qualitative approach. This study utilizes documentation analysis as its primary data collection method, involving thorough reading and systematic evaluation of the textbook content. The findings indicate the following distribution of cognitive levels across the questions: C1 (Remembering) accounted for 14 questions (15.7%), C2 (Understanding) for 28 questions (31.5%), C3 (Applying) for 15 questions (16.9%), C4 (Analyzing) for 13 questions (14.6%), C5 (Evaluating) for 1 question (1.1%), and C6 (Creating) for 18 questions (20.2%). These results reveal a lack of diversity and proportionality in the distribution of cognitive levels, underscoring an imbalance in the representation of higher-order thinking skills.